Identifikasi Brand Loyalty (Study on Honda motorcycle namely Mega Pro): (Studi Pada Motor Honda Merek Mega Pro) - Aris Munandar; Yen Efawati (Asosiasi Ahli Administrasi Indonesia, 2020)
The increase in market competition between two-wheeled vehicle manufacturers demands them to issue a variety of brands to suit consumer tastes. One of the brands is the Mega Pro brand which is made by Honda manufacturers. This research identifies consumers' loyalty to certain brands. The objects of this research are users of the Mega Pro, a brand of two-wheeled vehicles. There are a total of 100 respondents. The research data are analyzed using multiple regression, and the method that is used in this research is the survey method. The results of the study show that opposition brand loyalty, sharing brand stories, and helping in brand use are the factors that determine brand loyalty.